Self-Compassion and Peer Social Support: Do They Influence Self-Efficacy in Career Decision Making of Generation Z Students? - Madani, Wildan; Ihsan, Helli; Zakariyya, Farhan (Jurnal Kajian Bimbingan dan Konseling, 2024)
This study aims to determine the effect of self-compassion and peer social support on career decision-making self-efficacy (CDMSE) among Generation Z college students in Indonesia. This study uses quantitative methods with a regression analysis approach. Sampling was conducted using non-probability sampling techniques with an accidental sampling approach. This study involved 367 active college students from Generation Z, aged 18-24, residing or studying in the metropolitan area of Greater Bandung. Greater Bandung was chosen as the research location because it represents the characteristics of Generation Z in Indonesia. The city is a center of education and culture with diverse higher education institutions that attract students from across the country. Data was collected through a Likert-scale questionnaire, using scales that had been previously adapted and developed to measure self-compassion, peer social support, and CDMSE. Data analysis was conducted using multiple linear regression analysis. The results indicated that self-compassion and peer social support, both individually and simultaneously, positively influenced career decision-making self-efficacy among Generation Z. This suggests that students with higher levels of self-compassion and social support from peers tend to have greater confidence in making career decisions.